2005
DOI: 10.1021/je0503204
|View full text |Cite
|
Sign up to set email alerts
|

Speeds of Sound, Densities, and Isentropic Compressibilities of 1-Chlorohexane at Temperatures from (293.15 to 413.15) K and Pressures up to 200 MPa

Abstract: Experimental speeds of sound and densities are presented for the liquid phase of 1-chlorohexane. The measurements were carried out along seven isotherms from (293.15 to 413.15) K at pressures from saturation up to 200 MPa. The speed of sound was measured by a pulse-phase echo ultrasonic device at a frequency of (1 and 5) MHz with an uncertainty of ± 0.2 %. The density was measured by an acoustic piezometer with an uncertainty of ± 0.3 %. The experimental results have been used to calculate isentropic compressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…These procedures have been described in great detail in previous studies. 4,5 The highest temperature limit of measurements was defined by the boundary of a thermal stability of the substances around 413.15−423.15 K. The results are displayed in Tables S2 and S3.…”
Section: ■ Experimental Methods and Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…These procedures have been described in great detail in previous studies. 4,5 The highest temperature limit of measurements was defined by the boundary of a thermal stability of the substances around 413.15−423.15 K. The results are displayed in Tables S2 and S3.…”
Section: ■ Experimental Methods and Resultssupporting
confidence: 71%
“…This time we report experimental and interpolated data on thermophysical properties of 1-chloroheptane and 1-iodoheptane at 216.08 ≤ T ≤ 423.1 K and 0.1 ≤ P ≤ 196.1 MPa. The current analysis covers also the previously published results for 1-iodohexane, 4 1chlorohexane, 5 and 1-chloropropane 6 in similar P−T ranges, along with the volumetric properties of 1-alkyl bromides 7,8 and the eminent 9 data 10−13 of Percy Williams Bridgman at very high pressures. Unfortunately, no elevated pressure data are available in open sources for the medium-chain 1-alkyl fluorides.…”
Section: ■ Introductionsupporting
confidence: 60%
“…The temperature of samples placed into the thermostat (the absolute error of temperature stabilization is equal to ±0.05 K), which was measured by the platinum resistance thermometer providing the absolute error 0.01 K. The corrections respectively to the temperature and pressure dependence of the acoustic path were taken into account; see more details on the experimental setup and methodology elsewhere. 12,13 The isobaric heat capacity was measured by the industrial dynamical calorimeter ITC p -400 at atmospheric pressure. The resulting calculations of the isobaric heat capacity gave results, which have the relative error not exceeding ±5% over the whole temperature region explored.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…Within the single phase region, the measurements of the density and the speed of sound were evaluated along isotherms with the step 20 K. The external pressure was produced by the dead-weight pressure gauge MP-2500 with the step 10 MPa with the relative error ±0.02%. The temperature of samples placed into the thermostat (the absolute error of temperature stabilization is equal to ±0.05 K), which was measured by the platinum resistance thermometer providing the absolute error 0.01 K. The corrections respectively to the temperature and pressure dependence of the acoustic path were taken into account; see more details on the experimental setup and methodology elsewhere. , …”
Section: Experimental Methodsmentioning
confidence: 99%
“…Bolotnikov et al [45][46][47][48] and Hasanov et al 49,50 reported the u(T,P) for mainly liquid n-alkanes. Daridon and colleagues 51-68 have measured u(T,P), for ethers, esters and n-alkanes.…”
Section: Speed Of Sound In Liquid Organic Compoundsmentioning
confidence: 99%